Antimicrobial drug resistance affects broad changes in metabolomic phenotype in addition to secondary metabolism - Derewacz, Dagmara K; Goodwin, Cody R; McNees, C Ruth; McLean, John A; Bachmann, Brian O (Proceedings of the National Academy of Sciences - PNAS, 2013)
Bacteria develop resistance to many classes of antibiotics vertically, by engendering mutations in genes encoding transcriptional and translational apparatus. These severe adaptations affect global transcription, translation, and the correspondingly affected metabolism. Here, we characterize metabolome scale changes in transcriptional and translational mutants in a genomically characterized Nocardiopsis, a soil-derived actinomycete, in stationary phase. Analysis of ultra-performance liquid chromatography-ion mobility-mass spectrometry metabolomic features from a cohort of streptomycin- and rifampicin-resistant mutants grown in the absence of antibiotics exhibits clear metabolomic speciation, and loadings analysis catalogs a marked change in metabolic phenotype. Consistent with derepression, up to 311 features are observed in antibiotic-resistant mutants that are not detected in their progenitors. Mutants demonstrate changes in primary metabolism, such as modulation of fatty acid composition and the increased production of the osmoprotectant ectoine, in addition to the presence of abundant emergent potential secondary metabolites. Isolation of three of these metabolites followed by structure elucidation demonstrates them to be an unusual polyketide family with a previously uncharacterized xanthene framework resulting from sequential oxidative carbon skeletal rearrangements. Designated as "mutaxanthenes," this family can be correlated to a type II polyketide gene cluster in the producing organism. Taken together, these data suggest that biosynthetic pathway derepression is a general consequence of some antibiotic resistance mutations.